Moderate Gain Luenberger-Like Observer for Lipschitz Nonlinear Dynamics - Cunha, Sergio B. (Journal of Applied Nonlinear Dynamics, 2026)
Nonlinear systems state estimation has been an active research topic for some decades, since most nonlinear dynamics control algorithms require complete knowledge of the dynamic states and measuring all the states is often unfeasible. This note reviews former results and introduces a new methodology for determining the gains of a Luenberger-like observer employed with Lipschitz nonlinear dynamics. Some examples are presented to illustrate the use of the proposed algorithm and to compare it to recent solutions. This new methodology results in lower gains and enables the designer to determine the eigenvalues of the linear observer. It is shown that if the dynamics are in canonical form, this methodology can cope with a Lipschitz constant of any value.